Will the pact for the future advance a common global agenda on the challenges facing humanity? - Viviana Munoz Tellez; Danish; Abdul Muheet Chowdhary; Nirmalya Syam; Daniel Uribe Terán (South Centre, 2025)
At a time when multilateralism is needed more than ever to address the global challenges and rising geopolitical tensions, paradoxically, the capacity and delegated power of the United Nations (UN) to uphold a rule-based order to keep peace and security is being weakened. Even in an increasingly multipolar world, a retreat towards unilateralism by world powers masked as national sovereignty is dangerous and highly unfavourable for developing countries. In this light, the United Nations Pact for the Future, a new forward-looking agenda of commitments adopted by consensus by UN Member States in September 2024, is a welcome initiative. The Pact for the Future, nonetheless, is short in delivering commitments on transformative changes in global governance and solutions to the most pressing global challenges. This document briefly examines some of the actions and high-level commitments in the Pact of the Future to strengthen multilateral cooperation and provides recommendations for their implementation.
Keywords: 300; Friedenssicherung; Internationale Beziehungen; Welt